A Novel Hybrid Technique for Exchange Rate Forecasting - Salah, Abbas Mohamed; Rashid, Tarik Ahmed; Shareef, Shareef Maulod (Sulaimani Journal for Pure and Applied Sciences, 2015)
Exchange rate prices play a significant role in economic and financial systems. The precise forecasting of the exchange rate will aid to predict the situations of other aspects in the future. This offers useful information for economist traders to fulfill vital actions to eliminate risks that might lead to financial losses. One vital and common approach for forecasting is a quantitative technique. The quantitative technique is split into two approaches; fundamental and technical analysis. Both approaches have one different, which is the economic factor. The fundamental analysis uses economic factors while the other not, but both of them have drawbacks. In fundamental technique, the forecasters cannot understand the economic factors totally, the values and quantity of the factors unstable, while the technical analysis neglects the factors totally. This paper suggests a new technique which is appeared to be as a hybridized of the both techniques for forecasting exchange rate prices to overcome the issues mentioned above. The proposed technique makes new factors that have real values and have a real impact on the accurate result. It also derives the inputs and factors in the prediction models by a feature extraction technique which produces very accurate results.
Keywords: Exchange Rate; Forecasting; egovernment; Feature Extraction; Technical and Fundamental Analysis